Conflict to Reconciliation: Integrating Interfaith Dialogue, Peace Education, and Restorative Justice in Indonesia's Pluralistic Society - Thio Andriarta; Nazua Azura (Islamic Journal of Communication and Public Discourse, 2026)
Background: Interreligious conflict is a social phenomenon inseparable from the dynamics of multicultural society. This conflict is often rooted in differences in religious interpretation, political interests, socio-economic inequality, and is amplified by the dissemination of provocati ve information through mass media and social media.Objective: This study aims to analyze the factors causing interreligious conflict in Indonesia and examine effective resolution and reconciliation strategies for building peace between religious communities.Method: The research method used is a qualitative approach with library research. Findings and Implications: The results indicate that interreligious dialogue, peace education, the role of religious leaders, and the implementation of restorative justice and inclusive state policies are important elements in reducing the potential for conflict and building sustainable social reconciliation. This research is expected to serve as a reference in developing conflict resolution strategies based on religious values, humanity, and social justice.Conclusion: Despite the growing body of literature on interreligious conflict in Indonesia, previous studies have tended to examine causal factors or resolution strategies in isolation, without systematically integrating the structural, communicative, and reconciliatory dimensions into a unified analytical framework. This study addresses that gap by synthesizing these multidimensional perspectives within the Indonesian socio-religious context.